Metal Release of Standard and Fake Orthodontic Braces: An In Vitro Study - Nasir, Siti Hajjar; Mohamad Amran, Muhammad Syahmi; Abidin Mustaffar, Muhammad Muaz (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: The growing demand for orthodontic braces among Malaysians has led to the development of fake braces. These fake braces services are illegal and their brackets are reported to be of inferior quality. Fake braces are constantly being exposed to the saliva intraorally, hence they are susceptible to corrosion. This study was conducted to investigate the release of metal ions as a result of corrosion from standard and fake orthodontic braces immersed in artificial saliva of different pH. MATERIALS AND METHODS: A total of six different types of brackets (three from standard and three from fake braces) were immersed in containers containing 5 mL of artificial saliva of pH 4.9 and pH 7.8. The samples were collected for analysis on day 1, day 14, and day 28 using Inductively-Coupled Plasma Mass Spectrometry (ICPMS) to evaluate the amount of metal ion released. Statistical analysis was performed to isolate the significant difference of metal ions released between two types of braces in different pH solutions. RESULTS: The release of aluminum, nickel, chromium, manganese and copper were observed and analyzed. Fake braces released the highest concentration of chromium, manganese, and nickel ions in both artificial saliva as compared to standard braces. Brackets immersed in pH 4.9 released a higher number of ions compared to pH 7.8. CONCLUSION: This study showed that fake braces released the highest concentration of metal ions as compared to standard braces. Both time and pH influenced the release of metal ions from orthodontic brackets.